Minimizing DNA contamination by using UNG-coupled quantitative real-time PCR on degraded DNA samples: application to ancient DNA studies. (April 2005) - Pruvost, Mélanie; Grange, Thierry; Geigl, Eva-Maria
PCR analyses of ancient and degraded DNA suffer from their extreme sensitivity to contamination by modern DNA originating, in particular, from carryover contamination with previously amplified or cloned material. Any strategy for limiting carryover contamination would also have to be compatible with the particular requirements of ancient DNA analyses. These include the need ( i ) to amplify short PCR products due to template fragmentation; ( ii ) to clone PCR products in order to track possible base misincorporation resulting from damaged templates; and ( iii ) to avoid incomplete decontamination causing artifactual sequence transformation. Here we show that the enzymatic decontamination procedures based upon dUTP- and uracil-N-glycosylase (UNG) can be adapted to meet the specific requirements of ancient DNA research. Thus, efficiency can be improved to vastly reduce the amplification of fragments ≤100 bp. Secondly, the use of an Escherichia coli strain deficient in both UNG and dUTPase allows for the cloning of uracil-containing PCR products and offers protection from plasmid DNA contamination, and, lastly, PCR products amplified from UNG-degraded material are free of misleading sequence modifications.